Spontaneous Regression of Divided Nevus of the Eyelid Evaluated by Dermoscopy : Is it Hypopigmentation After Regression or Vitiligo - Wahyudi, Danang Tri; Aulia, Izzah; Hoemardani, Aida S. D.; Sutarjo, Agassi Suseno (UI Scholars Hub, 2020)
Background: Divided nevus, also known as “kissing nevus,” is a rare form of congenital melanocytic nevus that occurs on opposing margins of upper and lower eyelids. A paucity of literature on this rare anomaly exists, with most being case reports and series. Moreover, regression of this lesion was rarely reported. Case Illustration: We present a rare case of congenital divided nevus of the eyelid that regressed after eight years, confirmed with dermoscopy. A six-year-old boy presented to the Dharmais National Cancer Hospital with two pigmented macules on the upper and lower right eyelid since birth. A year ago, the lesions started gradually disappearing and were replaced by a hypopigmented area. We evaluated the clinical and dermoscopic findings for two consecutive years. The dermoscopy showed pseudopigment networks, surrounded by a hypopigmented area resembling a halo. The pigmented lesions cleared with no residual lesions. Discussion: The dermoscopic findings of the patient resemble a solar lentigo characterized by pseudopigment networks, a feature caused by the relatively flattened rete ridge on the face. The hypopigmented area reflects a regression process, like the halo nevus, and is accompanied by leukotrichia of the eyelashes, a feature usually found in patients with vitiligo. Regression of the divided nevus is related to an autoimmune process. A similar mechanism was also found in vitiligo. Since no atypical findings were present in this patient, we recommend only observation. Conclusion: Divided nevus is a rare case. We present a case of congenital divided nevus of the eyelid that regressed spontaneously. Clinical and dermoscopic findings of hypopigmented regression area were similar with vitiligo, which might share similar pathological mechanisms.